Galectin-9 promotes natural killer cells activity via interaction with CD44 - Rahmati, Amirhossein; Bigam, Steven; Elahi, Shokrollah (Frontiers in Immunology, 2023)
Natural killer (NK) cells are a potent innate source of cytokines and cytoplasmic granules. Their effector functions are tightly synchronized by the balance between the stimulatory and inhibitory receptors. Here, we quantified the proportion of NK cells and the surface expression of Galectin-9 (Gal-9) from the bone marrow, blood, liver, spleen, and lungs of adult and neonatal mice. We also examined the effector functions of Gal-9+NK cells compared with their Gal-9- counterparts. Our results revealed that Gal-9+NK cells are more abundant in tissues, in particular, in the liver than in the blood and bone marrow. We found Gal-9 expression was associated with enhanced cytotoxic effector molecules granzyme B (GzmB) and perforin expression. Likewise, Gal-9 expressing NK cells display greater IFN- and TNF- expression than their negative counterparts under hemostatic circumstances. Notably, the expansion of Gal-9+NK cells in the spleen of mice infected with E. coli implies that Gal-9+NK cells may provide a protective role against infection. Similarly, we found the expansion of Gal-9+NK cells in the spleen and tumor tissues of melanoma B16-F10 mice. Mechanistically, our results revealed the interaction of Gal-9 with CD44 as noted by their co-expression/co-localization. Subsequently, this interaction resulted in enhanced expression of Phospho-LCK, ERK, Akt, MAPK, and mTOR in NK cells. Likewise, we found Gal-9 preferentially interacts with CD44high in human NK cells. Therefore, our results highlight the important role of Gal-9 via CD44 in NK cell activation, which suggests Gal-9 is a potential new avenue for the development of therapeutic approaches to modulate NK cell effector functions.